How is deep vein thrombosis diagnosed and managed in UK and Australian emergency departments?. Issue 11 (21st October 2005) - Sampson, F C; Goodacre, S; Kelly, A-M; Kerr, D
Abstract : Background: Recent research has identified technologies that may be of value in the diagnosis and management of deep vein thrombosis (DVT). We aimed to survey current practice in the United Kingdom (UK) and Australia to determine the extent to which these technologies have been implemented in these two healthcare systems. Methods: We undertook a postal survey of 255 hospitals in the UK and 89 hospitals in Australia, requesting details of individual diagnostic tests, use of diagnostic algorithms, and management of DVT. Results: We received replies from 186/255 UK hospitals (73%) and 84/89 of Australian hospitals (94%). Ultrasonography and laboratory based d -dimer were the most commonly available tests. We received 43 different algorithms from 51 hospitals. With only a very few exceptions, DVT diagnosis was ruled in by positive venography or positive ultrasound without venographic confirmation. By contrast a variety of different criteria were used to rule out DVT. Most algorithms used a combination of low clinical risk and negative d -dimer to rule out DVT, but some required all patients to receive ultrasound or venography. Few ruled out on the basis of low clinical risk or negative d -dimer alone. Low molecular weight heparins were overwhelmingly the treatment of choice for established DVT. Most departments (214/264; 81%) offered outpatient treatment. Conclusion: Recently developed technologies for the diagnosis and treatment of DVT have been widely implemented in the UK and Australia. Variation in practice, and thus presumably uncertainty, seems to be greatest in relation with the criteria used to rule out DVT.